A COMPARATIVE ANALYSIS OF SERBIA AND THE EU MEMBER STATES IN THE CONTEXT OF THE NETWORKED READINESS INDEX VALUES - Soldić-Aleksić, Jasna; Stankić, Rade (Economic Annals, 2015)
Nowadays it is generally accepted that information and communication technologies (ICT) are important drivers and ‘enabling’ technologies that have a broad impact on many sectors of the economy and social life. Therefore, measuring the level of ICT development, their economic and social impact, and the country’s readiness to use them are of great importance. In this paper we present the conceptual framework of the Networked Readiness Index (NRI) proposed by the World Economic Forum, and analyse the relative position of Serbia and its ‘distance’ from the EU member states in the domain of NRI indicator variables. For this purpose we have applied the Kohonen Self-Organizing Map (the SOM algorithm), which provides the visual image, as a virtual map, of observed countries and their groupings. The resulting SOM map indicates that in the complex NRI space, Serbia is located in a group of EU states that includes Romania, Croatia, Bulgaria, Cyprus, Greece, Italy, Poland, the Czech Republic, and the Slovak Republic. In comparison to other countries, this group shows the poorest performance in the NRI landscape. In addition, our empirical analysis points to the areas in which policy intervention can boost the impact of ICT on Serbian economic development and growth.